Impact of strengthening exercises on hip stability and functional mobility in patient with posterior hip dislocation - Pranjal Dixit (Advanced International Journal for Research, 2026)
Background:- The most common cause of posterior hip dislocation, a rare but dangerous orthopaedic injury, is high-energy trauma from car crashes. Restoring hip stability, avoiding comorbidities, and improving functional results all depend on early reduction followed by systematic physiotherapy rehabilitation. • Case Description:-Four weeks following closed reduction of a severe posterior hip dislocation experienced in a car accident, a 24-year-old male patient arrived at the Orthopaedic and Physiotherapy Department. The patient experienced severe pain (VAS 8/10), limited hip range of motion, muscle weakness (MMT 3/5), poor gait, and decreased functional mobility at the time of the initial evaluation. A 20-second Timed Up and Go (TUG) test and a Harris Hip Score of 55 were used as functional outcome measures. •Intervention :-The patient participated in an eight-week, five-day structured physiotherapy rehabilitation program that included range-of-motion exercises, balance training, gait training, and functional mobility exercises in addition to progressive hip and core strengthening exercises (bridging, straight leg raises, clamshells, hip abduction, quadriceps and gluteal setting exercises, knee raises, and hip flexor/extensor strengthening). •Result :-The patient showed significant improvement after rehabilitation. Hip flexion improved from 70° to 120°, hip abduction from 20° to 45°, muscular strength grew from MMT 3/5 to 5/5, TUG improved from 20 to 10 seconds, and the Harris Hip Score climbed from 55 to 90. Pain decreased from 8/10 to 2/10. Significant improvements were also seen in gait pattern, hip stability, and independence in daily life activities. •Conclusion :- In a patient with posterior hip dislocation, a planned physiotherapy program that prioritized progressive strengthening exercises successfully enhanced hip stability, muscle strength, range of motion, discomfort, gait, and functional mobility. This case emphasise how crucial early, closely monitored therapy is to a successful functional recovery following a catastrophic posterior hip dislocation.